Effect of Cinnamon Leaves (Cinnamomun burmannii) Extract in the Diet on Growth Performances and Survival Rate of Milkfiish (Chanos chanos) Juveniles - Marelin Kusumastuti; Subandiyono Subandiyono; Sri Hastuti (Departemen Akuakultur FPIK UNDIP, 2021)
One of the problems that often occur in milkfish farmers is the inadequate use of diet protein for growth. Due tu a larger proportion of diet protein is utilized as energy by fish. Cinnamomun leaves extract (C. burmannii) contains the active ingredients of polyphenol and synnamaldehyde compounds which are thought to threaten body contents from diet fats and carbohydrates. So that diet fats and carbohydrates are expected to be used more efficiently as a substitute for diet protein energy. The purpose of this study was to examine the role of polyphenol and synnamaldehyde compounds in cinnamomun (C. burmannii) leaves extract to increase the growth and survival of milkfish (C. chanos). The study consisted of four treatments, namely A (0 g/kg diet), B (0.5 g/kg diet), C (1 g / kg diet), and D (2 g/kg diet) the treatment was repeated three times. The results showed that the additions of cinnamomun leaves extract in the diet at different doses had a significant effect (P <0,05) on the level of diet consumption, efisiency diet utilizen, protein efficiency ratio, and relative growth rate, but the same (P >0,05) for the survival rate. Treatment B (0.5 g/kg diet) gave the highest results for level of diet consumption, efisiency diet utilizen, protein efficiency ratio, and relative growth rate, wich are 77.18 ± 1.41 g, 47.32 ± 10.32%, 1.18 ± 0.26%, and 0.95 ± 0.26%. Based on the results obtained, the best dose of cinnamomun leaves extract (C. burmannii) is 0.5 g/kg diet. Keyword: Cinnamomun Leaves, Extract, Growth., Survival Rate, Milkfish, Juvenille